Comparing a single-day swabbing regimen with an established 3-day protocol for MRSA decolonization control. (May 2018) - Frickmann, H.; Schwarz, N.G.; Hahn, A.; Ludyga, A.; Warnke, P.; Podbielski, A.
Abstract: Objectives: Success of methicillin-resistant Staphylococcus aureus (MRSA) decolonization procedures is usually verified by control swabs of the colonized body region. This prospective controlled study compared a single-day regimen with a well-established 3-day scheme for noninferiority and adherence to the testing scheme. Methods: Two sampling schemes for screening MRSA patients of a single study cohort at a German tertiary-care hospital 2 days after decolonization were compared regarding their ability to identify MRSA colonization in throat or nose. In each patient, three nose and three throat swabs were taken at 3- to 4-hour intervals during screening day 1, and in the same patients once daily on days 1, 2 and 3. Swabs were analysed using chromogenic agar and broth enrichment. The study aimed to investigate whether the single-day swabbing scheme is not inferior to the 3-day scheme with a 15% noninferiority margin. Results: One hundred sixty patients were included, comprising 105 and 101 patients with results on all three swabs for decolonization screening of the nose and throat, respectively. Noninferiority of the single-day swabbing scheme was confirmed for both pharyngeal and nasal swabs, with 91.8% and 89% agreement, respectively. The absolute difference of positivity rates between the swabbing regimens was 0.025 (−0.082, 0.131) for the nose and 0.006 (−0.102, 0.114) (95% confidence interval) for the pharynx as calculated with McNemar's test for matched or paired data. Compliance with the single-day scheme was better, with 12% lacking second-day swabs and 27% lacking third-day swabs from the nostrils. Conclusions: The better adherence to the single-day screening scheme with noninferiority suggests its implementation as the new gold standard.